The discourse of broadcast news : - Montgomery, Martin (Routledge, 2007)
In this timely and important study Martin Montgomery unpicks the inside workings of what must still be considered the dominant news medium: broadcast news. Drawing principally on linguistics, but multidisciplinary in its scope, The Discourse of Broadcast News demonstrates that news programmes are as much about showing as telling, as much about ordinary bystanders as about experts, and as much about personal testimony as calling politicians to account. Using close analysis of the discourse of television and radio news, the book reveals how important conventions for presenting news are changing, with significant consequences for the ways audiences understand its truthfulness. Fully illustrated with examples and including detailed examination of the high profile case of ex-BBC journalist Andrew Gilligan, The Discourse of Broadcast News provides a comprehensive study which will challenge our current assumptions about the news. The Discourse of BroadcastNews will be a key resource for anyone researching the news, whether they be students of language and linguistics, media studies or communication studies.